Success and failure in M&As : Is there a place for a paradigm change? Evidence from the Israeli hi-tech industry - Zaks, Ofer (Economics and Business Review, 2016)
The consistent growth of mergers and acquisitions (M&As) activity around the world in the last decade, and the volume of capital involved in such transactions, stand in sharp contrast to the high failure rates evident in M&As. The inconsistency amongst empirical findings on M&As performance is based on a variety of settings and on different measurements investigated under the generic label M&As. This paper claims that we need to differentiate between general M&A and those involving technology firms acquisition. The combination of the drive, the dynamic process and the human capital capabilities which characterize the latter, is expected to result in a more successful result than was reported. Hi-tech innovative acquirers can benefit from buying small, start-up firms by adding valuable resources, increasing market power and initiating strategic renewal.